2015
DOI: 10.1007/s40610-015-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in Transcriptional Regulation

Abstract: Transcriptional gene silencing guided by small RNAs is a process conserved from protozoa to mammals. Small RNAs loaded into Argonaute family proteins direct repressive histone modifications or DNA cytosine methylation to homologous regions of the genome. Small RNA-mediated transcriptional silencing is required for many biological processes, including repression of transposable elements, maintaining the genome stability/integrity, and epigenetic inheritance of gene expression. Here we will summarize the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…Long non-coding RNAs, also known as lncRNAs, have recently received wide attention due to their rising functions in development and diseases 8 , 9 . Such RNA transcripts are characterized by more than 200 nucleotides that have no capacity of encoding proteins 10 . Increasing evidence has shown that lncRNAs are involved in several levels, including transcription and post-transcription 11 - 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs, also known as lncRNAs, have recently received wide attention due to their rising functions in development and diseases 8 , 9 . Such RNA transcripts are characterized by more than 200 nucleotides that have no capacity of encoding proteins 10 . Increasing evidence has shown that lncRNAs are involved in several levels, including transcription and post-transcription 11 - 13 .…”
Section: Introductionmentioning
confidence: 99%
“…During the post-genome period, lncRNAs have become a focus of study in the regulation of histone acetylation, gene methylation, post-transcription translation, and other biological processes [ 23 - 25 ]. Recently, many more lncRNAs have been confirmed to play critical roles in regulating the physiological behavior of malignant cancers, including breast, pancreatic, gastric, lung, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNAs have attracted much attention in various areas of study to elucidate the complex mechanisms of multiple cellular processes, especially in cancer [ 20 - 22 ]. The functions of lncRNAs mainly include regulation of gene methylation, transcriptional activation, conjugation with mRNAs and miRNAs to affect translation progression and other processes [ 23 - 25 ]. Normally, the relationships between lncRNAs and their neighboring coding genes include sense overlapping, antisense, intronic, divergent, and intergenic interactions [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are a form of RNA whose length is more than 200 nucleotides. They themselves do not encode proteins but participate in the regulation of gene expression and various biological processes [ 5 ]. LncRNAs can activate or inhibit the expression of target genes by directly binding to the target genes, or be involved in histone modification or recruitment of transcription factors.…”
Section: Introductionmentioning
confidence: 99%